Dielectric and electromagnetic interference shielding properties of nano‐silicon carbide/montmorillonite and graphene nanoplatelets filled polyvinylidene fluoride/poly(3, 4‐ethylenedioxythiophene)‐block‐poly(ethylene glycol) blend nanocomposites. Issue 8 (7th December 2022) - Thanasekaran, Gayathri; Ahamed, M. Basheer; Deshmukh, Kalim; Kaldec, Jaroslav
Abstract: Herein, hybrid polymer nanocomposite films comprising polyvinylidene fluoride (PVDF) and poly(3, 4‐ethylenedioxythiophene)‐block‐poly(ethylene glycol) (PEDOT‐block‐PEG) as matrices and silicon carbide nanoparticles (SiC NPs), montmorillonite (MMT) nanoclay, and graphene nanoplatelets (GNPs) as nanofillers were fabricated by solution casting. The structural, morphological, and thermal characteristics of the nanocomposite films were assessed using Fourier transform infrared spectroscopy (FTIR), x‐ray diffraction (XRD), scanning electron microscope (SEM), thermogravimetric analyzer (TGA), and differential scanning calorimetry (DSC). The SEM results show the homogeneous distribution of nanofillers within the polymer matrix. The dielectric behavior and electromagnetic interference shielding efficiency (EMI SE) of the nanocomposites were also analyzed. The maximum dielectric constant ( ε ) and dielectric loss (tan δ ) obtained are 47.77 and 12.08, respectively, at lower frequency (50 Hz, 150°C). The maximum EMI SE was observed to be 16.8 dB in the Ku‐band region (12–18 GHz) for the nanocomposites with 20 wt% SiC, 8 wt% MMT, and 2 wt% GNPs loading. The EMI shielding was found to be absorption dominant and originated from the formation of a conductive network between hybrid nanofillers within the PVDF/PEDOT‐block‐PEG blend thereby improving the EMI SE values. These results suggest that PVDF/PEDOT‐block‐PEG/SiC/MMT/GNPs nanocomposites can be used as an efficient EMI shielding material. Abstract : Synthesis procedure of PVDF/PEDOT‐block‐PEG/SiC/MMT/GNPs nanocomposite films.